PEMAKNAAN INTERAKSI VIRTUAL PEMBERI GIFT POINTS PADA PENGGUNA LOWER SELF ESTEEM APLIKASI TANTAN DI PALEMBANG - Adelina Nurul Hikmah Lubis; Sepriadi Saputra; Sonia Nurprameswari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
ABSTRACT The use of live streaming features in dating applications such as Tantan has led to the phenomenon of male users giving gift points to female hosts, which not only reflects entertainment activity but also serves as a form of symbolic communication, especially for users with lower self esteem. This study aims to explore how virtual interaction is interpreted by gift Point givers toward users with lower self esteem within the context of the Tantan application in Palembang. The research applies the theory of symbolic interactionism by George Herbert Mead and Herbert Blumer, which emphasizes that social meaning is constructed through interaction processes and the use of communication symbols. This study employs a qualitative method with a phenomenological approach, collecting data through in-depth interviews with seven male informants who have used Tantan for over a year and actively give gift points via its live streaming feature. The results show that in terms of motivation, gift points are given as a form of appreciation toward hosts who are personally appealing, in the context of action, gift points function as non-verbal communication tools representing the desire to interact, in self-perception, the act helps build a sense of existence and social acceptance, in trust, the decision to give is influenced by assessments of the host's worthiness and image, in social influence, giving behavior is shaped by trends and community recommendations, and in terms of satisfaction, positive responses from hosts determine the user's comfort and continued engagement with the application. Keywords: Gift points, Tantan, virtual interaction, lower self esteem, symbolic interactionism.